2015
DOI: 10.1039/c4sm01890g
|View full text |Cite
|
Sign up to set email alerts
|

Shape transformations of toroidal vesicles

Abstract: Morphologies of genus-1 and 2 toroidal vesicles are studied numerically by dynamically triangulated membrane models and experimentally by confocal laser microscopy. Our simulation results reproduce shape transformations observed in our experiments well. At large reduced volumes of the genus-1 vesicles, obtained vesicle shapes agree with the previous theoretical prediction, in which axisymmetric shapes are assumed: double-necked stomatocyte, discoidal toroid, and circular toroid. However, for small reduced volu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…The modulus k is determined from the length ratio, For small buckling amplitudes, F cv2 can be expanded for 1 − L z /L ed ≪ 1 as in Eq. (7). Figure 6(b) shows an example of F cv obtained by Eqs.…”
Section: Simple Geometric Model Of Polygonal Tubesmentioning
confidence: 99%
“…The modulus k is determined from the length ratio, For small buckling amplitudes, F cv2 can be expanded for 1 − L z /L ed ≪ 1 as in Eq. (7). Figure 6(b) shows an example of F cv obtained by Eqs.…”
Section: Simple Geometric Model Of Polygonal Tubesmentioning
confidence: 99%
“…where λ 1 ≤ λ 2 ≤ λ 3 are the eigenvalues of the gyration tensor of the vesicle. The asphericity is the degree of deviation from a spherical shape: α sp = 0 for spheres, α sp = 1 for thin rods, and α sp = 0.25 for thin disks [18,23]. The spherical stomatocyte and discocyte have α sp ≃ 0 and 0.2, respectively.…”
Section: Genus-5 Vesiclesmentioning
confidence: 99%
“…Phase diagrams of genus-1 and genus-2 vesicles were constructed by Jülicher et al [13][14][15] for symmetric shapes. Recently, we found that nonaxisymmetric shapes such as elliptic and handled discocytes also exist in equilibrium for genus-1 vesicles [18].…”
Section: Introductionmentioning
confidence: 99%
“…Fluid vesicles are simulated by a dynamically triangulated surface method [32,[35][36][37]. Since the details of the potentials are described in Ref.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…Since the details of the potentials are described in Ref. [32] and the general features of the triangulated membrane can be found in Ref. [36], we briefly describe the membrane model here.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%